An examination of tissue engineered scaffolds in a bioreactor. Issue 1 (October 2016) - Niedermeyer, Angela; Zhou, Bei; Dursun, Gözde; Stoffel, Marcus; Artmann, Aysegül; Markert, Bernd
Abstract: Replacement tissues, designed to fill in articular cartilage defects, should exhibit the same properties as the native material. The aim of this study is to foster the understanding of, firstly, the mechanical behavior of the material itself and, secondly, the influence of cultivation parameters on cell seeded implants as well as on cell migration into acellular implants. In this study, acellular cartilage replacement material is theoretically, numerically and experimentally investigated regarding its viscoelastic properties, where a phenomenological model for practical applications is developed. Furthermore, remodeling and cell migration are investigated. (© 2016 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)